Monitoring of intraportal liver cell application in children - Meyburg, Jochen; Hörster, Friederike; Schmidt, Jan; Pöschl, Johannes; Hoffmann, Georg F.; Schenk, Jens-Peter (Cell transplantation, 2010)
Despite recent advances and promising results in children, liver cell transplantation (LCT) should still be regarded as an experimental therapy. Several substantial complications are known from animal studies and individual patients. However, safety data on liver cell infusion in children are scarce. We used LCT in four children of different ages (3 weeks to 11 years, 3?40 kg) and underlying diseases [acute liver failure (n = 1), urea cycle disorders (n = 2), and Crigler-Najjar syndrome (n = 1)]. Vital parameters, portal vein flow (PVF), portal vein pressure (PVP), and liver enzymes were measured every 5 min during cell application and hourly thereafter between applications. An application protocol with discontinuation rules depending on changes in PVF and PVP was developed and successfully applied. Application was feasible in all children despite the catastrophic overall condition of the patient with acute liver failure. No application-related changes in vital parameters were found, and none of the children experienced clinical signs of portal vein thrombosis, pulmonary embolism, or anaphylactic reactions. Time courses for changes in PVF, PVP, and liver enzymes were obtained. Thorough monitoring of portal vein pressure and duplex sonography according to a defined protocol is likely to increase safety of cell application in pediatric LCT.
Gesehen am 20.04.2023